Anterior cingulate cortex and dorsal hippocampal glutamate receptors mediate generalized fear in female rats - Adkins, Jordan M. (Psychoneuroendocrinology, 2019)
Exhibiting fear to non-threatening cues or contexts—generalized fear—is a shared characteristic of several anxiety disorders, which afflict women more than men. Female rats generalize contextual fear at a faster rate than males and this is due, in part, to actions of estradiol in the dorsal CA1 hippocampus (dCA1). To understand the mechanisms underlying estradiol’s effects on generalization, we infused estradiol into the anterior cingulate cortex (ACC) or ventral CA1 hippocampus (vCA1) of ovariectomized (OVX) female rats. Estradiol acts within the ACC, but not the vCA1, to promote generalized fear. We next examined if AMPA or NMDA receptor antagonists (NBQX, APV) infused into the dCA1 or the ACC of female rats could block generalized fear induced by systemic injections of estradiol. Immediate pre-testing infusions of NBQX or APV into either region eliminated estradiol-induced generalization. Specific blockade of GluN2B receptors with infusions of Ro 25–6981 into the dCA1 or ACC also eliminated generalized fear. Our results suggest that in addition to the dCA1, the ACC is an important locus for the effects of estradiol on fear generalization. Moreover, within these regions, AMPA and NMDA-GluN2B receptors are necessary for estradiol-induced generalization of fear responses, suggesting a critical involvement of glutamatergic transmission. Furthermore, we identified a novel role for GluN2B in mediating the effects of estradiol on generalized fear in female rats. These data potentially implicate GluN2B receptors in more general forms of memory retrieval inaccuracies, and form the foundation for exploration of glutamate receptor pharmacology for treatments of anxiety disorders involving generalization.